PEMANFAATAN MEDIA SOSIAL DALAM PROMOSI POTENSI WISATA BAHARI CILACAP JAWA TENGAH - Yuni Tresnawati (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2018)
Social  networking  sites  or  social  media  today  is  already  familiar  to  the  public,  almost  every  individual  using social media from the young to the old either for bussiness  or just to connect with friends. One positive impact is as a communication medium can facilitate the search for information. For example many who use social media search for news that is actual or even looking for a trendy tourist destination through uploads of users of social media.  This  can  indirectly  assist  the  promotion  of  tourist  attractions.  Therefore,  this  study  will  discuss  more deeply about Social Media Utilization in Promotion of Marine Tourism Potential in Cilacap , Central Java .  The concepts  used  are  the  utilization  of  social  media  and  marketing  communications  and  7  C  Framework Communication  using  constructivist  paradigm  with  qualitative  descriptive  approach.  The  proper  use  of  social media  includes  persuasion  and  emotional  attachment  to  increase  trust  of  followers  of  the  account  against  the information  provided.  The  development  of  world  tourism  is  very  rapid,  making  Indonesia    be  left  behind  by continuing to improve tourism  in this country. Although Indonesia's tourism  contribution continues to increase every  year,  it still  needs to be  improved so as not to be  left behind  from other countries whose tourism  is  also growing. Increased one of them is to attract more tourists (both abroad and archipelago) to Indonesia. The way to go  is  of  course  through  promotion.  Therefore,  the  improvement  of  innovation  in  the  field  of  promotion  must continue to be done.Keywords: Digital, Social Media, Promotion, Tourism